Upper Tract Urothelial Carcinoma With Renal Vein and Inferior Vena Cava Tumor Thrombus Mimicking Renal Cell Carcinoma: A Case Report and Literature Review - Yifan LI; Shangchun FEI; Ming ZHOU; Ye YAO; Xiang PAN; Zhong LIU; Lei WANG; Yi LIU; Lezhong QI; Qibing FAN (国际转化医学杂志（英文版）, 2019)
A 67-year-old man presented with asymptomatic gross hematuria for one year. The results of routine laboratory examinations and urinalysis suggested that mild anemia, hematuria and urinary tract infection. An enlarged right kidney was found by abdominal enhanced computed tomography (CT) and magnetic resonance imaging scan, which revealed inhomogeneous enhanced renal masses in the upper pole and pelvis of right kidney with extension into the right renal vein and inferior vena cava (IVC). Chest CT showed several nodular masses. According to the radiographic imaging findings, we suggested the diagnosis to be metastatic renal carcinoma with extension to renal pelvis, vein and IVC. Then, the patient underwent open right radical nephrectomy and thrombectomy without regional lymphadenectomy. The pathologic report was consistent with a high-grade urothelial carcinoma, with squamous epithelial differentiation involving the renal vein and IVC. Thus, this was a rare case of upper tract urothelial carcinoma (UTUC). To our knowledge, this is one of 51 UTUC with venous invasion reported worldwide.